Intergovernmental fiscal relations, theoretical aspects and Poland's experience - Beata Guziejewska (e-Finanse: Financial Internet Quarterly, 2013)
The distribution of public revenues is one of the fundamental elements in the shaping of the system of public finance in any country. The process is difficult from both the political and economic points of view. Also the objective conditions make the ideal distribution impossible and any solution results in a greater or lesser fiscal imbalance. An attempt to solve the problems of vertical and horizontal fiscal imbalance and consequences of a greater contribution of territorial self-government tasks and finance leads to complex fiscal relations between the state and the territorial self-government. The aim of this paper is to point out the basic characteristics of the financing system of the local government and the areas of fiscal relations between the national and local government in Poland against the traditional principles of fiscal federalism. Statistical measures of financial independence of territorial self-government entities and their restrictions have also been presented here. The paper ends with conclusions which synthetically present the current problems in fiscal relations in Poland and conclusions de lege ferenda.
Keywords: H70; H71; H77; 330; public finance; fiscal relations; territorial self-government finance